Does proprioception of knee improve after various forms of training in osteoarthritis of knee? - Naresh Bhaskar, Raj; Soumendra, Saha; Srilekha, Saha; Hazliza, Razali; Nur Yanti Haryana, Othman (2019)
The present study was aimed to investigate the role of various forms of training in improving the proprioception of the knee joint in patients with osteoarthritis of knee. Sixty participants (male and female) with knee Osteoarthritis of Grade II & III (Kellgren-Lawrence criteria) in the age range of 50-73 years were recruited from the Department of Orthopedics, Hospital Universiti Sains Malaysia. The recruited participants were taken to the Exercise and Sports science laboratory and the laboratory of School of Medical Sciences, Universiti Sains Malaysia for baseline assessment. The level of proprioception was assessed with the aid of isokinetic device BIODEX 4 System Pro. The participants were randomly categorized into four groups (Gr.) (Viz. Gr. A, Gr. B, Gr. C and Gr. D) and thus each group consisted of 18 participants. Gr. A participants received Conventional Physiotherapy consisting of strengthening exercises; stretching exercises and range of motion exercises. Gr. B received Isokinetic Training at velocities of 90° and 150°/second. Gr. C participants received EMG Biofeedback training with Mega ME 6000 device and Gr.D participants recieved a combined intervention of isokinetic training and EMG Biofeedback. The training protocol was designed for 25 - 30 minutes per session; 2 sessions per week for 10 weeks (20 sessions). The assessment was done after 5th week of training (mid term) and after 10th week of training (post) following baseline assessment protocol. A follow up assessment was performed after the 14th and 18th week to assess the after effect of training. Meanwhile the participants were not given any training after the 10 week period. They were also adviced not to get engaged in any sort of physical training, exercise or sport programme. Repeated measure of ANOVA revealed that, all interventions helped in improving the proprioception of the knee joint however post hoc analyses implicated that a combined intervention of Isokinetic Training and EMG biofeedback was beneficial in enhancing proprioception than the conventional physiotherapy (P<.05).